Graduation Ceremony 2001 - Part 1
Recording of the CEU Graduation Ceremony of the class of 2000/2001. It starts with images of the students and the teachers getting prepared for the ceremony, putting on the caps and gowns and taking pictures on the halls of CEU and in the CEU Auditorium. The ceremony starts with the procession and continues with Prof. Stefan Messman the Pro-Rector of the CEU greeting the audience and inviting the President and Rector of the University Yehuda Elkana to present his introductory remarks. After Prof. Yehuda Elkana’s speech Prof. Stefan Messman welcomes János Martonyi the Minister of Foreign Affairs of Hungary to deliver his speech. Next, Prof. Gábor Klaniczay, Rector at Collegium Budapest is invited to speak about the academic achievements of Prof. Bronisław Geremek (Polish social and political historian) who immediately afterwards accepts the “CEU Open Society Prize” from George Soros (Founder of CEU and Chairman of the Board of Trustees). Before the conferring of the master and doctoral degrees and the commencement speech, there is a short musical interlude on violin by Ádám Banda.